E-Arbitration: A Way Forward to Improve Quality and Service Delivery in Malaysian Dispute Resolution Industry - Mohammad Azam Hussain; Mohamad Fateh Labanieh; Nazli Mahdzir (International Journal of Supply Chain Management, 2020)
The Malaysian legislative framework governing traditional arbitration still relies on the traditional method. Parallel with the current COVID-19 pandemic, the question arises here, does traditional arbitration improves the quality and service delivery in the Malaysian arbitration industry? By using legal research methodology, this contribution endeavours to examine how electronic arbitration (hereinafter referred to as e-arbitration) could be a potential cure for improving the quality and service delivery in the Malaysian arbitration industry. The collected data then is analytically and critically scrutinised using content analysis method. This contribution found that COVID-19 pandemic shows clearly the disability in the Malaysian arbitration industry. Therefore, the contribution recommended that the Malaysian legislators should renovate the existing arbitration laws in order to totally legalise e-arbitration because of its ability to improve the quality and service delivery in the Malaysian arbitration industry. Finally, the contribution concluded that e-arbitration system should be considered as a supplementing to the traditional arbitration system.